Franklin smoke : wood, fire, food - Franklin, Aaron; Mackay, Jordan (Ten Speed Press, 2023)
"The ultimate guide to live-fire cooking and smoking at home, with recipes that will have you grilling up meat, vegetables, fish, and more like a Texas pitmaster-from the James Beard Award-winning team behind the New York Times bestseller Franklin Barbecue"--